2021
DOI: 10.1080/19336918.2021.1963574
|View full text |Cite
|
Sign up to set email alerts
|

The roles of serotonin in cell adhesion and migration, and cytoskeletal remodeling

Abstract: Serotonin is well known as a neurotransmitter. Its roles in neuronal processes such as learning, memory or cognition are well established, and also in disorders such as depression, schizophrenia, bipolar disorder, and dementia. However, its effects on adhesion and cytoskeletal remodelling which are strongly affected by 5-HT receptors, are not as well studied with some exceptions for e. g. platelet aggregation. Neuronal function is strongly dependent on cell-cell contacts and adhesion-related processes. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 125 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…It is worth mentioning that the differential proteins screened in the healthy group compared with the BD group were similarly enriched in the biological process of cell adhesion. At the same time, John Jayakumar JAK et al [71] found that serotonin plays an important role in mental illness and the positive and negative effects of neuropsychiatric drugs through cell-associated adhesion, including depression, bipolar disorder, and schizophrenia. A sample of the group of 11 bipolar patients was compared to a sample of the group of 13 depressed patients.…”
Section: Identification and Functional Analysis Of Urine Proteome In ...mentioning
confidence: 99%
“…It is worth mentioning that the differential proteins screened in the healthy group compared with the BD group were similarly enriched in the biological process of cell adhesion. At the same time, John Jayakumar JAK et al [71] found that serotonin plays an important role in mental illness and the positive and negative effects of neuropsychiatric drugs through cell-associated adhesion, including depression, bipolar disorder, and schizophrenia. A sample of the group of 11 bipolar patients was compared to a sample of the group of 13 depressed patients.…”
Section: Identification and Functional Analysis Of Urine Proteome In ...mentioning
confidence: 99%
“…The 5‐HT plays many critical roles during development, including the regulation of various cellular processes, such as cell division, differentiation, migration, myelination, synaptogenesis, neurite sprouting and dendritic pruning (Daubert & Condron, 2010; Jayakumar & Panicker, 2021; Lesch & Waider, 2012; Rojas et al, 2014), leading to the shaping of neural circuits in the brain. Because SSRIs can cross the placental barrier, exposure during pregnancy can lead to alterations in the brain (Hendrick et al, 2003) and behavior (Olivier et al, 2013) of developing fetuses.…”
Section: Introductionmentioning
confidence: 99%